MERAH DAN PENGARUHNYA TERHADAP BIOKIMIA TANAH PADA PERCOBAAN POT MENGGUNAKAN TANAH ULTISOL - Antonius, Sarjiya; Sahputra, Rozy Dwi; Nuraini, Yulia; Dewi, Tirta Kumala (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTUltisol dominated about 25% of the total land area in Indonesia. It has the potential to be used as agricultural land and shallot plants have a considerable prospect to be cultivated in ultisol soil. Ultisol generally has not been handled properly. It needs some specific treatments due to the low nutrient contents, caused by the intensive leaching process. One of the effort to overcome the soil quality problems that occur in ultisol soils (high soil acidity, average pH <4.50, high Al saturation, and low macronutrient content such as P, K, Ca, Mg, and organic material content) is treated by the using the soil conditioner such as the supplying of organic materials in the form of compost and biochar. In this work, the biological organic fertilizer was also applied to increase microorganism activity in the soil. The experimental design used in this work was completely random design which has 8 combinations of soil treatment, compost, biochar and bio-organic fertilizer. Soil parameters measured were pH, C-Organic, P-Available, total bacterial population, soil respiration, and phosphomonoesterase enzyme activity. The agronomy parameters of shallot were also measured. The results showed that treatment of compost, biological organic fertilizer, and biochar have significant effect to increase soil microorganism activity in the form of total population of bacteria, soil respiration, P-Available and pH. The treatment also had a significant effect on supporting plant height at 2 and 6 MST, number of leaves at 2 MST, wet weight and dry weight of tubers. Keywords: biochar, bio-organic fertilizer, soil microorganism activity, shallot, ultisol